Effects of Progressive Muscle Relaxation on Concentration and Performance Scores of 10m Shooters - Novan, Novrizal Achmad; Irianto, Nandya Indriana Adha; Komarudin, Komarudin; Awwaludin, Patriana Nurmansyah (Universitas Pendidikan Indonesia, 2021)
Shooting skills are very complex, and often athletes have to be faced with situations that require one shot to get a perfect score and need to maintain concentration and the pull of the trigger. This study aimed to analyze the difference in progressive muscle relaxation (PMR) exercise on increasing concentration and performance scores of 10-meter shooting. A total of 12 athletes (seven female dan five males) in Purwakarta were recruited for this study. They were randomly assigned to the two groups, the PMR group (n = 6) and the control (n = 6). The instruments used were the Concentration Grid Test to measure concentration while the 60 shots of both men and women of 10-meter shooting scores for a performance test. Data analysis using MANCOVA was performed using shooting scores and concentration as the dependent variable and covariates to determine their performance. They can be differentiated based on conventional training methods, progressive muscle relaxation, and the interaction of these factors. The results of the MANCOVA indicated a significant main effect for exercise methods, and it was revealed that differences in exercise methods had a significant effect on concentration and shooting scores. When athletes are faced with the demands of top performance, PMR training is a very economical but efficient and effective strategy for dealing with several problems. This helps athletes self-control and focus their attention during stressful situations and can be used to maintain physical, technical, and mental balance.Â